OPTIMALISASI BIAYA TRANSPORTASI PENDISTRIBUSIAN KERAMIK MENGGUNAKAN MODEL TRANSPORTASI METODE MODIFIED DISTRIBUSITION (STUDI KASUS : PT. INDAH BANGUNAN) - Ayulinansyah, S; Jaya, A I; Sahari, A (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2018)
This study was conducted to obtain optimal costs of transportation in the distribution of Ceramics at PT. Indah Bangunan Palu. This research is carried out by several steps such as: making the model transportation of obtained the data, determining the initial solution by the method of Least cost, and finding the optimal solution with Modified Distribution (MODI) method. The research results showed that an initial solution is ð‘…ð‘. 53.919.000 and the optimal solution is ð‘…ð‘. 53.756.000. On the other hand the transportation cost from the company before optimization is ð‘…ð‘. 62.126.000. This indicates that PT. Indah Bangunan Palu can optimize the costs of transport for the distribution of ceramics on September 2016 with a cost savings of ð‘…ð‘. 8.370.000 or 13%